Pyloric Perforation with Gastro-duodenal Artery Pseudo Aneurysm Due to Peptic Ulcer Disease in a Toddler: Case Report with Review of Literature - Ruchi Mishra; Shivangi Tetarbe; Parag Janardhan Karkera; Ira Shah (Indian Pediatrics Case Reports)
Background: With increasing use of endoscopy in children, peptic ulcer disease (PUD) is being diagnosed more frequently and perforation of PUD is also being reported. However, most such cases are reported in older children and adolescents. We report a rare occurrence of perforated PUD in a young child associated with the rupture of pseudoaneurysm of gastroduodenal artery (GDA). Clinical Description: A 3-year-old boy presented with abdominal pain and nonbilious vomiting, exhibiting peritoneal signs upon examination. An X-ray erect abdomen confirmed pneumoperitoneum. During the hospital stay, the patient also developed melaena. Management and Outcome: Emergency laparotomy revealed a small perforation between the pylorus and the first part of the duodenum, which was successfully repaired. However, postoperatively, the patient continued to experience massive melaena, accompanied by a significant drop in hemoglobin. Angiography indicated an irregular GDA with a small pseudoaneurysm which was then angioembolized. The patient recovered and was discharged on proton-pump inhibitors. A gastroduodenoscopy after 2 weeks revealed Helicobacter pylori (HP) infection, which was treated as per guidelines. Conclusion: This case report underscores the importance of considering perforated PUD in a child with pneumoperitoneum, and HP testing in all children with PUD. Rupture of a pseudoaneurysm of GDA may be a complication of PUD, which if promptly treated, can be life-saving.